2013
DOI: 10.1186/1471-244x-13-236
|View full text |Cite
|
Sign up to set email alerts
|

Depression among women with obstetric fistula, and pelvic organ prolapse in northwest Ethiopia

Abstract: BackgroundThe prevalence of depression is not well studied among women with pelvic floor disorders. Hence, this study aimed to determine the prevalence of depression and its associated factors among women with pelvic floor disorders.MethodsA cross-sectional study was conducted among 306 women with one or more of the advanced pelvic floor disorders who attended at the gynaecologic outpatient clinic of Gondar university referral hospital in the six months data collection period. Women who complained of urinary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 23 publications
(46 reference statements)
0
43
2
2
Order By: Relevance
“…We were surprised to find the low prevalence of depressive symptoms in our study cohort after fistula repair. In other contexts of fistula patients, pre‐operative rates of depression have ranged from 59 to 97% . Another study also found that women with residual incontinence have higher rates of depression (100%) after repair compared with those who are not leaking (29%) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We were surprised to find the low prevalence of depressive symptoms in our study cohort after fistula repair. In other contexts of fistula patients, pre‐operative rates of depression have ranged from 59 to 97% . Another study also found that women with residual incontinence have higher rates of depression (100%) after repair compared with those who are not leaking (29%) .…”
Section: Discussionmentioning
confidence: 97%
“…In other contexts of fistula patients, pre-operative rates of depression have ranged from 59 to 97%. 30,31 Another study also found that women with residual incontinence have higher rates of depression (100%) after repair compared with those who are not leaking (29%). 32 However, in that study, the follow-up time after repair was only 2 weeks.…”
Section: Limitationsmentioning
confidence: 97%
“…Similarly, studies in Nigeria10 and Nepal11 showed that different forms of POP have been affecting women’s health and quality of life alarmingly 12. Women with POP have been suffering from significant social problems such as sexual relationships problems, functional impairment, depression, and poor quality of life 1317. In Ethiopia, gynecological problems are important health problems affecting maternal health outcomes and women’s productivity 18.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the majority of women with fistula have described symptoms of mood disorders, including suicidal ideations . Yeakey found that much of this was a result of being unable “to fulfil social expectations of them as women, wives and mothers”.…”
Section: Introductionmentioning
confidence: 99%